The Influence of Peer Conformity and Pocket Money on Students' Lifestyle in Higher Education - Mutiara Iriani; Riyo Riyadi; Noor Ellyawati; Sutrisno Sutrisno (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study aims to analyze the influence of peer conformity and pocket money on university students' lifestyles. Today's students often feel compelled to follow current lifestyle trends, influenced by factors such as peer pressure and the availability of pocket money. This study examines whether peer conformity and pocket money, either partially or simultaneously, affect students' lifestyles. The study adopts a quantitative approach with a saturated sampling technique involving 70 respondents. Data were collected using questionnaires and analyzed through multiple linear regression using SPSS version 26. Hypothesis testing was conducted using t-tests, F-tests, and the coefficient of determination (R²). The findings indicate that peer conformity and pocket money each have a positive and significant partial influence on students' lifestyles. Simultaneously, these two factors also positively and significantly influence lifestyle choices. The coefficient of determination (R²) reveals that 72.2% of students' lifestyle variance can be explained by peer conformity and pocket money, while the remaining 27.8% is influenced by other factors not examined in this study. This research highlights the important role of peer interactions and financial resources in shaping students' lifestyle choices, offering valuable insights for educational institutions and parents in guiding students toward balanced and sustainable lifestyle decisions.